Layanan Bimbingan Kelompok dalam Membentuk Sikap Jujur Melalui Pembiasaan - Syifa Nur Fadilah (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2019)
The content of this article is about group guidance services to foster an honest attitude through conditioning. Honest attitude is a positive attitude that is owned by individuals, honesty can be formed through the environment in which the individual interacts. Group Guidance Service is one of the efforts of the counseling service program, which in the process of group guidance services utilizes group dynamics as a form of guidance effort by providing information about honesty material as an effort to habituate group guidance participants so that group guidance participants take advantage of their honest attitude to habituation in the environment where the individual is located. The method used refers to the type of qualitative-descriptive research using a library research approach, with the ultimate goal of obtaining a general and comprehensive picture of the efforts of group guidance services in forming honest attitudes.